2020
DOI: 10.1080/1461670x.2020.1731706
|View full text |Cite
|
Sign up to set email alerts
|

Is News Surveillance Related to Cancer Knowledge in Underserved Adults? Testing Three Versions of the Cognitive Mediation Model

Abstract: The cognitive mediation model (CMM) proposes indirect paths to news learning such that news surveillance increases news learning through attention to the news and elaboration about the news. But there is a need for additional research that tests key postulates of the CMM especially for media targeting underserved populations. The present study tested three versions of the CMM to model ethnic newspaper learning within a low-income, Spanish-speaking population (N = 150). The original CMM was not supported by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
2
2
1
Order By: Relevance
“…Even if individuals have higher surveillance gratification, meaning that they want to learn about their social environment during the pandemic, they might have different levels of attention to online versus traditional media (Ho & Yang, 2018), or newspaper, TV news, TV programs, and online news (Yang et al, 2017). Nevertheless, consistent with the previous literature (Eveland Jr. et al, 2003; Jensen et al, 2020), surveillance gratification exerted a positive direct impact on elaboration ( β = 0.46, p < 0.001), as well as the most substantial total effect ( β = 0.50, p < 0.001). Therefore, the intention to understand travel issues in the social environment motivates people to engage in the two types of information processing, that is, media attention and elaboration, which further improves individuals' pandemic and travel health knowledge and prepares them for travel decision‐making.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Even if individuals have higher surveillance gratification, meaning that they want to learn about their social environment during the pandemic, they might have different levels of attention to online versus traditional media (Ho & Yang, 2018), or newspaper, TV news, TV programs, and online news (Yang et al, 2017). Nevertheless, consistent with the previous literature (Eveland Jr. et al, 2003; Jensen et al, 2020), surveillance gratification exerted a positive direct impact on elaboration ( β = 0.46, p < 0.001), as well as the most substantial total effect ( β = 0.50, p < 0.001). Therefore, the intention to understand travel issues in the social environment motivates people to engage in the two types of information processing, that is, media attention and elaboration, which further improves individuals' pandemic and travel health knowledge and prepares them for travel decision‐making.…”
Section: Discussionsupporting
confidence: 91%
“…Study results showed that surveillance gratification did not significantly impact media attention, which contradicts the previous studies (e.g., Eveland Jr. et al, 2003;Eveland Jr., 2001; Ho , 2013Jensen et al, This contradiction may be due to the unique characteristics of the COVID-19 context that some other motivations (e.g., anticipated interaction) work more dominantly compared to surveillance gratification. Another reason might be related to different media types, as we only tested the overall media attention.…”
Section: Conc Lusion a N D I M Pl Icat Ions Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In health, factual knowledge about diseases, such as the symptoms, causes, diagnosis, and treatment, helps stay physically and mentally healthy. Indeed, when equipped with accurate facts, people can engage themselves and the people around them in healthy practices (Jensen et al, 2020).…”
Section: Knowledge and Miscalibrationmentioning
confidence: 99%
“…Our focus on surveillance motivation and news media use, in relation to knowledge, is well-grounded in the existing literature that theorizes their roles in learning from the news (e.g., Eveland, 2001Eveland, , 2002Jensen, 2011). Research rooted particularly in the cognitive mediation model has shown that surveillance motivation and news media use have independent and indirect positive influences on political and health knowledge (e.g., Eveland, 2001;Jensen et al, 2020). While Eveland (2001) found that surveillance motivation influences news media use, Jensen (2011) modified the cognitive mediation model by proposing an interactive effect of surveillance motivation and news attention and showed that those with high levels of surveillance motivation and attention to health news were more likely to process, and as a result, comprehend a news story.…”
Section: Surveillance Motivation As a Moderatormentioning
confidence: 99%